Incorruptible bodies Christology, Society, and Authority in Late Antiquity - Moss, Yonatan 1977- (Oakland, California University of California Press, 2016)
"Incorruptible Bodies examines a fateful theological controversy that raged in the eastern Roman empire in the early sixth-century. The controversy, whose main participants were the anti-Chalcedonian leaders Severus of Antioch and Julian of Halicarnassus, centered on whether or not Jesus' body was corruptible prior to its resurrection from the dead. Viewing the controversy in light of late antiquity's multiple images of the 'body of Christ,' Yonatan Moss reveals the underlying political, ritual, and cultural stakes of this debate and its long-lasting effects"--Provided by publisher.
Introduction : dissension among the dissenters -- Severus of Antioch and the separation of the churches -- Christology, ecclesiology and liturgy : a "stereoscopic approach" -- Contesting the body of Christ -- The incorruptibility debate between Julian and Severus : a literary survey -- Severus on the body of Christ -- Julian on the body of Christ -- Staking out the differences -- Patriarch Severus: separatist or ecumenicist? -- John Rufus and his "charismatic" coalition : anti-Chalcedonian separatism -- John of Tella's extra-canonical ordination campaign -- How to receive a heretic : pre-Chalcedonian and post-Chalcedonian views -- Severus' case against rechrismation : unity vs. purity -- The Eucharist and the diptychs -- Severus' theology of the Eucharist -- Julian's theology of the Eucharist : a reconstruction -- The diptychs -- The stereoscopic approach in action -- The textual body of the patristic past -- Severus writing the fathers -- Julian writing the fathers -- Julian reading the fathers -- Severus reading the fathers -- Overcoming exile -- Severus, Julian and friends -- Incorruptible : anti-Chalcedonians on the body of Severus.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Person and offices -- History -- To 1500.; Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Severus, -- of Antioch, -- approximately 465-538.; Julianus, -- Bishop of Halicarnassus, -- active 6th century; Church history -- Primitive and early church, ca. 30-600; 276 -- Griekse patrologie--SEVERUS ANTIOCHENUS -- Patrologie grecque--SEVERUS ANTIOCHENUS